Pengaruh Kualitas Kerja dan Efektivitas Kerja Terhadap Produktivitas Kerja yang di Moderasi oleh Motivasi Kerja Pada Dinas Perindustrian Perdagangan Koperasi dan Usaha Kecil Kota Lhokseumawe - Darni, Surya; Febriansyah, Sutan (Jurnal EMT KITA, 2024)
The advancing times exert pressure on organizations to encourage and manage their human resources (HR) effectively since HR serves as the fundamental asset for an organization to achieve its objectives. Managing HR is an obligation that organizations must undertake, led by their leaders, to reach their goals and targets. This research is a quantitative study aimed at investigating whether job quality and work effectiveness influence job productivity, moderated by work motivation. The study's population consists of all employees of the Department of Industry, Trade, Cooperatives, and Small Businesses of Lhokseumawe City, totaling 61 individuals. The sampling technique employed was saturation sampling. Both primary and secondary data were used in this study. Data collection utilized a questionnaire technique, involving direct questioning of the respondents who served as the study's sample. Data analysis was conducted using the Multiple Regression Analysis (MRA) approach. The research findings indicate that job quality does not affect job productivity, while work effectiveness can influence job productivity. However, work motivation was found to be unable to moderate the relationship between job quality and work effectiveness on job productivity.